2017
DOI: 10.1002/ijc.30746
|View full text |Cite
|
Sign up to set email alerts
|

Coffee consumption and the risk of colorectal cancer by anatomical subsite in Japan: Results from the HERPACC studies

Abstract: Consumption of coffee, a popular beverage worldwide, has been associated with lower colorectal cancer (CRC) risk. Although CRC exhibits different biological characteristics by anatomical subsite, the possibly heterogeneous impact of coffee on CRC by anatomical subsite has remained unclear. Here, we conducted two case-control studies to examine the association between coffee consumption and CRC risk as well as risk by anatomic subsite among Japanese using data from the Hospital-based Epidemiological Research Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 37 publications
1
17
0
Order By: Relevance
“…Beverages like tea (green, black) and coffee have also proven to be protective against the occurrence of carcinoma. A study from Japan has also been consistent with this finding, stating the role of coffee in reducing the risk of colon and rectal carcinoma (Senda Nakagawa et al 2017). This is consistent with another study where coffee and tea intake has proven beneficial in case of oral and pharyngeal carcinoma (Garavello et al 2009), while hot maté drinking has been related to increased risk in studies from Argentina and Brazil.…”
Section: Diet and Supplementationsupporting
confidence: 85%
“…Beverages like tea (green, black) and coffee have also proven to be protective against the occurrence of carcinoma. A study from Japan has also been consistent with this finding, stating the role of coffee in reducing the risk of colon and rectal carcinoma (Senda Nakagawa et al 2017). This is consistent with another study where coffee and tea intake has proven beneficial in case of oral and pharyngeal carcinoma (Garavello et al 2009), while hot maté drinking has been related to increased risk in studies from Argentina and Brazil.…”
Section: Diet and Supplementationsupporting
confidence: 85%
“…However, studies suggest that the ethanol (but not the other components of alcoholic beverages) matters primarily for cancer risk, regardless of the types of alcoholic beverages . In addition, we could not assess other explanatory variables such as menopausal hormone therapy (for female breast cancer), a family history of cancer, diet (eg, coffee and red meat), physical activities, and ALDH2 genotypes . In the JPHC study, alcohol‐related bladder cancer risk was observed in male “flushers” (who are supposed to have polymorphisms in ALDH2 enzyme) but not in male nonflushers .…”
Section: Discussionmentioning
confidence: 99%
“…9 In addition, we could not assess other explanatory variables such as menopausal hormone therapy (for female breast cancer), a family history of cancer, diet (eg, coffee and red meat), physical activities, and ALDH2 genotypes. 9,14,33 In the JPHC study, alcoholrelated bladder cancer risk was observed in male "flushers" (who are supposed to have polymorphisms in ALDH2 enzyme) but not in male nonflushers. 9 In the assessment of how robust our estimate (OR for ever drinkers, 1.18) was to potential unmeasured and uncontrolled confounding, the E-value was 1.64.…”
Section: Discussionmentioning
confidence: 99%
“…49,50 In contrast, coffee consumption is inversely proportional to the risk of LSCRC. 51 Cigarette smoking and diabetes mellitus are associated with an increased risk of RSCC. [52][53][54] There were some limitations to our study.…”
Section: Discussionmentioning
confidence: 99%